Prices and heterogeneous search costs. - Moraga‐González, José Luis; Sándor, Zsolt; Wildenbeest, Matthijs R. (RAND Journal of Economics (Wiley-Blackwell))
We study price formation in a model of consumer search for differentiated products in which consumers have heterogeneous search costs. We provide conditions under which a pure-strategy symmetric Nash equilibrium exists and is unique. Search costs affect two margins-the intensive search margin (or search intensity) and the extensive search margin (or the decision to search rather than to not search at all). These two margins affect the elasticity of demand in opposite directions and whether lower search costs result in higher or lower prices depends on the properties of the search cost density.